CONSIDERATIONS CONSERNING THE SPATIAL DISTRIBUTION OF ANNUAL PRECIPITATION QUANTITIES IN THE HYDROLOGICAL BASIN OF JIJIA - L. APOSTOL; D. BURUIANĂ; D. Machidon (Aerul şi Apa: Componente ale Mediului, 2013)
Precipitations are, besides other climate elements, a defining parameter for individualization of the climate in certain regions and a crucial influence in the climatic features and geographical landscape in its ensemble. Also, with a great temporal and spatial variability, precipitations induce some significant changes in human social activities. The hydrographical basin of Jijia is situated in Moldavian Plateau the subunit of the Moldavian Plain. Because it is lowered by 200 - 300m from adjacent subunits, it appears to be like a depression (valley) with altitudes between 270-300 m. Under the conditions of relatively uniform lithologie with little possibility of underground water storage or supply from river flow, precipitations are the main power supply units and underground water in the Jijia basin. Spatial and temporal variability of this parameter involve extreme great heterogeneity and other components of the hydrological balance (evapo-transpiration, drainage, infiltration), which increases the difficulty in determinations of quantitative small spaces and short intervals. Spatial distribution of precipitation posts and weather stations, in their large number (37) has enabled us to make a regular grid of points (including stations in the surrounding area and the basin). All this combined with a long study period over 50 years (1960-2011), allowed us to make a map of spatial distribution and annual amounts of precipitation in Jijia basin.